A case series of histoplasmosis patients with elevated serum soluble interleukin-2 receptor levels. Issue 9 (September 2017) - Hirayama, Tatsuro; Takazono, Takahiro; Iwata, Kazuma; Senju, Hiroaki; Shimazaki, Takaharu; Tashiro, Masato; Saijo, Tomomi; Tanaka, Takeshi; Nakamura, Shigeki; Imamura, Yoshifumi; Kojiro, Maiko; Miyazaki, Taiga; et al.
Abstract: Histoplasmosis is a common endemic mycosis that is usually asymptomatic but occasionally results in severe illness. Histoplasmosis and its causative agent, Histoplasma capsulatum, are found worldwide but rarely in Japan. In recent years, however, the number of histoplasmosis patients in Japan has increased. In addition, to our knowledge, there are no previous reports of increased serum soluble interleukin-2 receptor (sIL-2R) levels in patients with histoplasmosis. We report a case series of histoplasmosis in three Japanese temporary workers in Manzanillo, Mexico. All three patients developed a persistent high fever and general fatigue. Laboratory tests showed increased C-reactive protein levels and mild liver dysfunction. All patients also showed increased soluble interleukin-2 receptor (sIL-2R) levels. Chest computed tomography revealed multiple nodules in both lung fields. All patients were positive for serum anti- Histoplasma antibodies, and two patients were positive for Histoplasma on polymerase chain reaction tests. After treatment that included antifungals, their conditions gradually improved and laboratory data normalized. Although one patient developed respiratory failure, this patient recovered with antifungal therapy in combination with methylprednisolone. Serum sIL-2R levels in all patients gradually declined to normal levels, indicating their recovery from Histoplasma infection. From our experience with these patients, sIL-2R levels may be a useful biomarker for patients with histoplasmosis.